2002
DOI: 10.1023/a:1014426530935
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Key factors that contribute to the aerodynamic properties of aerosol particles are found in Stokes' law. These factors may be monitored or controlled to optimize drug delivery to the lungs. Predictions of the aerodynamic behavior of therapeutic aerosols can be derived in terms of the physical implications of particle slip, shape and density. The manner in which each of these properties have been used or studied by pharmaceutical scientists to improve lung delivery of drugs is readily understood in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(51 citation statements)
references
References 13 publications
1
46
0
2
Order By: Relevance
“…It is of interest, from both safety and efficacy standpoints, to consider the extent and rate of deaggregation of nanoparticle agglomerates since this will influence a variety of elements of disposition from dissolution rate to route of elimination or access to the target site for therapy or off-target site for toxicity [54]. A micro-agglomerated nanoparticle construct may exhibit low density, in which case it may have two potentially desirable properties: the first being its small aerodynamic particle size in relation to its geometric size, which is predicted by Stokes' law [55]. In principle, the longer nanoparticles which remain aggregated are more likely to behave as microparticles with respect to clearance mechanisms.…”
Section: Fate Of Microparticles and Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest, from both safety and efficacy standpoints, to consider the extent and rate of deaggregation of nanoparticle agglomerates since this will influence a variety of elements of disposition from dissolution rate to route of elimination or access to the target site for therapy or off-target site for toxicity [54]. A micro-agglomerated nanoparticle construct may exhibit low density, in which case it may have two potentially desirable properties: the first being its small aerodynamic particle size in relation to its geometric size, which is predicted by Stokes' law [55]. In principle, the longer nanoparticles which remain aggregated are more likely to behave as microparticles with respect to clearance mechanisms.…”
Section: Fate Of Microparticles and Nanoparticlesmentioning
confidence: 99%
“…However, their low density may mean that their geometric size is too large for macrophage uptake [43]. In addition, their large surface area may increase the dissolution rate for soluble particles [55]. In turn, this will have an effect on the pharmacokinetics of drug appearance in the systemic circulation.…”
Section: Fate Of Microparticles and Nanoparticlesmentioning
confidence: 99%
“…To increase budesonide diffusion within lung fluid, we developed nanoporous microparticles 31 (NPMPs) composed of budesonide and a mucokinetic, ambroxol hydrochloride, to be inhaled as a dry 32 powder. Budesonide/ambroxol-HCl particles were formulated by spray drying and characterised by var- 33 ious physicochemicals methods.…”
mentioning
confidence: 99%
“…This seems to be because the inhalation profile of DPI is affected by various factors including particle size, morphology electrostatic charge and inhalation condition. 10,12,[24][25][26] Therefore, there is a need for preparation and characterization of series of powder samples that are different in surface properties but similar in other properties and compare them under the same inhalation condition.Mechanofusion can modify the surface energy of lactose carrier particles without drastic change of the particle size and can make the particle shape round to lessen the differences.Inverse gas chromatography (IGC) has been utilized to examine the effect of surface energy on the inhalation behavior of DPI. We reported that mechanofusion on a lactose carrier changed the carrier's surface condition and the inhalation properties of DPI formulations containing the lactose carrier and Compound A.…”
mentioning
confidence: 99%
“…This seems to be because the inhalation profile of DPI is affected by various factors including particle size, morphology electrostatic charge and inhalation condition. 10,12,[24][25][26] Therefore, there is a need for preparation and characterization of series of powder samples that are different in surface properties but similar in other properties and compare them under the same inhalation condition.…”
mentioning
confidence: 99%